2016
DOI: 10.1016/j.rcim.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Addressing perception uncertainty induced failure modes in robotic bin-picking

Abstract: We present a comprehensive approach to handle perception uncertainty to reduce failure rates in robotic bin-picking. Our focus is on mixed-bins. We identify the main failure modes at various stages of the bin-picking task and present methods to recover from them. If uncertainty in part detection leads to perception failure, then human intervention is invoked. Our approach estimates the confidence in the part match provided by an automated perception system, which is used to detect perception failures. Human in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 71 publications
0
12
0
1
Order By: Relevance
“…The part was placed in the bin and the boundary of the part was marked such that the part could be placed in the same position and orientation for later parts of the experiment. The point cloud of the scene was captured and a user interface designed in MAT-LAB was used to estimate the pose of the part by manually docking the CAD model of the part in the point cloud [23]. The points belonging to the part were deleted from the point cloud and the point cloud of the CAD model was rendered at the pose of the part.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The part was placed in the bin and the boundary of the part was marked such that the part could be placed in the same position and orientation for later parts of the experiment. The point cloud of the scene was captured and a user interface designed in MAT-LAB was used to estimate the pose of the part by manually docking the CAD model of the part in the point cloud [23]. The points belonging to the part were deleted from the point cloud and the point cloud of the CAD model was rendered at the pose of the part.…”
Section: Resultsmentioning
confidence: 99%
“…They used a perception module to evaluate the outcome of pushing actions. In our previous work [23, 24], any failure in the automatic pose estimation was handled with the help of human assistance. The human operator used an interface to estimate the pose of the part and sent it back to the robot.…”
Section: Related Workmentioning
confidence: 99%
“…We will compliment this capability in the future by exploiting the KUKA robot's inbuilt force sensing and impedance control features to implement compliant control for handling postcollision scenarios. In our previous work, we have developed other modules including ontology for task partitioning in human-robot collaboration for kitting operations [55] and resolving perception uncertainties [56] and occlusions in robotic bin-picking in hybrid cells [57]. Future work consists of investigating how to integrate them into the development of hybrid work cells for assembly applications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a larger uncertainty of the starting point for the search of the hole center using F/T sensors led to increased search time [27]. Kaipa et al generated singulation strategies for binned parts and showed that the probability of a successful singulation diminished with increasing error of the part position [28]. Mahler et al reported that increased pose error of a part degraded the quality of grasp planning even after the application of sophisticated algorithms to reduce these errors [29].…”
Section: Related Workmentioning
confidence: 99%